Structure-activity relationships of tulipalines, tuliposides, and related compounds as inhibitors of MurA - Mendgen, Thomas; Scholz, Therese; Klein, Christian D. (Bioorganic & medicinal chemistry letters, 2010)
The enzyme MurA performs an essential step in peptidoglycan biosynthesis and is therefore a target for the discovery of novel antibacterial compounds. We report here the inhibition of MurA by natural products from tulips (tulipalines and tuliposides), and the structure-activity relationships of various derivatives. The inhibition of MurA can be related to antibacterial activity, and MurA is probably one of the relevant molecular targets of the tulipaline derivatives. MurA inhibition by this class of compounds depends on the presence of the substrate UNAG, which indicates non-covalent suicide inhibition as observed previously for cnicin. With respect to selectivity, however, the reactivity against arbitrary sulfhydryl groups, such as in glutathione, could not yet be sufficiently separated from MurA inhibition in the present dataset.
Gesehen am 14.04.2023